1979
DOI: 10.1002/path.1711290306
|View full text |Cite
|
Sign up to set email alerts
|

Squamous carcinoma of the colorectum and its genesis

Abstract: A case of pure aquamous carcinoma of the rectum is presented, and the literature reviewed. Squamous carcinomas of the colorectum are rare tumours which have clinicopathological features in common with adenocarcinomas. Evidence is presented to support the proposal that most tumours of the large intestine that consist partly or completely of squamous elements arise from areas of squamous differentiation in pre-existing adenomas. The pathogenesis of squamous carcinoma and adenosquamous carcinoma appears to be sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
172
1
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(178 citation statements)
references
References 22 publications
2
172
1
3
Order By: Relevance
“…The pathogenesis of these tumors is poorly understood but may involve squamous de-differentiation of a pre-existing adenocarcinoma or squamous metaplasia progressing to dysplasia and carcinoma as a result of a chronic inflammatory stimulus (1)(2)(3)(4)(5). In the present case, the presence of squamous metaplasia in the adjacent mucosa suggests the latter.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The pathogenesis of these tumors is poorly understood but may involve squamous de-differentiation of a pre-existing adenocarcinoma or squamous metaplasia progressing to dysplasia and carcinoma as a result of a chronic inflammatory stimulus (1)(2)(3)(4)(5). In the present case, the presence of squamous metaplasia in the adjacent mucosa suggests the latter.…”
Section: Discussionmentioning
confidence: 70%
“…Since then, less than 50 cases of SCC in the colon or rectum have been reported. In 1979, Williams et al (5) proposed the following three criteria that should be met before establishing a diagnosis of SCC: (a) metastasis from other sites to the colon must be excluded; (b) a squamous-lined fistula tract must not involve the affected bowel because it may be a source of SCC; and (c) SCC of the anus with proximal extension must be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…F. Michelassi пред-положил, что хроническое повреждение слизистой может стимулировать пролиферацию недетермини-рованных базальных клеток в плоскоклеточные [17]. Также в литературе описаны случаи нахождения участков плоскоклеточного рака в аденомах и адено-карциномах [18,19], что говорит в пользу теории о возможности развития плоскоклеточного рака как доминантного клона стволовых клеток другой злока-чественной опухоли [20]. Более распространенны тео рии, что это преимущественно радиоиндуцирован-ные опухоли [21] (хотя в нашем наблюдении этот фактор был исключен), а также метаплазия плоского эпителия [22].…”
Section: Discussionunclassified
“…In Japan, Murakami et al described the first case of a pure SCC of the colon in 1974 [13]. It has been suggested that a number of criteria must be satisfied before a diagnosis of primary squamous cell carcinoma of the large bowel is entertained [3,14,15]: (1) there must be no evidence in any other organ of a squamous cell carcinoma that might spread directly into the lower bowel or provide a source of intestinal metastases, (2) the affected bowel should not be involved in a fistulous tract lined with squamous cells (colocutaneous fistulas have been described in association with squamous cell cancer), (3) when squamous cell carcinoma occurs in the rectum, care must be taken to exclude origin from the anal canal (that is, there should be a lack of continuity between the lesion and the anal canal epithelium), and (4) SCC must be confirmed by histological analysis. Our case satisfied all the above criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, some represent extraordinarily rare lesions and may, thus, be the source of difficult decision-making in the clinical practice. Pure squamous cell carcinoma (SCC) is a histologic subtype of tumors of epithelial origin that is not uncommon in glandular organs such as lung and pancreas, but accounts for only 0.1 to 0.25 cases per 1,000 colorectal carcinomas [2][3][4][5]. After the first case report in 1919 [6], a total of 74 pure SCC of the colorectum and 147 of mixed squamous and adenosquamous cancer cases have been reported in the literature [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%